Efficient light-driven CO2 hydrogenation on Ru/CeO2 catalysts. Issue 24 (26th November 2018) - Quan, Fengjiao; Zhan, Guangming; Mao, Chengliang; Ai, Zhihui; Jia, Falong; Zhang, Lizhi; Gu, Honggang; Liu, Shiyuan
Abstract : An efficient catalysis system for light-driven CO2 hydrogenation was designed and the function mechanism of light was investigated. Abstract : Light-driven heterogeneous catalysis provides a promising way to accomplish chemical reactions by the use of light energy, which reduces the consumption of chemical energy sources. Here, we show that Ru/CeO2 catalysts exhibit high activity for the hydrogenation of CO2 to methane under illumination only, reaching high CO2 conversion (over 99.9%) and selectivity of methane (∼100%) at low temperature. In sharp contrast, less CO2 is converted at the same temperature when a traditional heating model is used. As revealed by the results, the enhanced conversion rate under illumination should not only be attributed to the light-induced thermo-heating. Further investigations by in situ IR analysis and theoretical calculation provide comprehensive understanding of the reaction mechanism, and the important role of light is revealed. It is expected that the combination of catalysts and light may afford new perspectives for CO2 hydrogenation.